HIV-related stress predicts depression over five years among people living with HIV - Liu, Zongyan; Chen, Xi; Li, Jie; Xie, Zhi; Huang, Yunxiang; Luo, Dan (Frontiers in Public Health, 2023)
Introduction: Extant literature has demonstrated significant associations between HIV-related stress, social support, and depression among PLWH. However, little research has been conducted on the changes in such associations over time. Our study aims to explore the longitudinal relationship between HIV-related stress, social support, and depression among PLWH over five years. Methods: 320 PLWH were recruited from Changsha Center for Disease Control and Prevention (CDC), Hunan Province, China. They were assessed for depressive symptoms, HIV-related stress, and social support within one month of HIV diagnosis, one year after diagnosis, and five years after diagnosis, respectively. Relationships between these variables were examined using a fixed effect model. Result: The prevalence of depressive symptoms within the first month, first year, and fifth years of HIV diagnosis was 35%, 12.2%, and 14.7%, respectively. Emotional stress (β: 0.730, 95% CI: 0.648, 0.811), social stress (β: 0.066, 95% CI: 0.010, 0.123), instrumental stress (β: 0.133, 95% CI:0.046, 0.221) positively predicted depression, while social support utilization (β: -0.176, 95% CI: -0.303, -0.049) negatively predicted depression.） Conclusion: Our study suggests that HIV-related stress and social support predict depressive symptoms over time among PLWH and that reducing HIV-related stress and improving social support in the early stages of diagnosis is extremely important in preventing depressive symptoms among PLWH.